A scoping review of problems and challenges faced by school leaders (2003–2019) - Tintoré, Mireia (2020)
The purpose of this scoping review is to analyse the literature concerning principals’ problems and challenges, beginning in 2003 and ending in 2019. The research team conducted an extensive search to locate relevant academic literature, comprising 17 years of research, and a total of 153 documents were analysed.According to the findings,most of the documents (71%) correspond tothe last six years (2014– 2019), and most are studies from Anglo-Saxon countries (55%). The results point to eight main categories related to thecomplex nature of the job (themanagement challenge, the complexity challenge and the learning challenge), and interactions with different stakeholders (problems with educational authorities and educational policy; the staff and teaching process; the students; the families and the school community; and the society). Although the importance given to each category varies from one context to another, problems concerning the complex nature of the job andwith the educational authorities and the educational policy are the most recurrent. A significant increase in the number and complexity of problems andchallenges throughout the timeswasnoticed,whichseemstoenhancetheneedfor changes in educational policies and the careful design and implementation of leadership training programmes.